From Technical Security to Human Awareness: A Bibliometric Review of Cybersecurity Education Research - Cindy Muhdiantini; Mega Fitri Yani; Istifa Shania Putri (RAM PUBLISHER, 2026)
The rapid advancement of information technology has increased cybersecurity threats, emphasizing the importance of education in building security awareness and human-centered defense capabilities. As research on cybersecurity education continues to grow, a systematic understanding of its research trends and thematic evolution is required. This study analyzes global research trends in cybersecurity education using a bibliometric approach. A total of 189 Scopus-indexed publications from 2020 to 2026 were analyzed using the bibliometrix R package and the Biblioshiny interface. The analysis examines annual publication growth, dominant keywords, evolving research topics, and geographical research contributions. The results indicate a steady increase in scientific production, confirming cybersecurity education as an expanding research domain. While technical topics such as network and data security remain prominent, recent research shows a clear shift toward education, training, and security awareness, highlighting the growing importance of human factors in cybersecurity. In addition, the findings reveal an imbalance in global research contributions and relatively limited international collaboration. This study provides a concise overview of the development and structure of cybersecurity education research and offers insights to support future studies, curriculum development, and policy formulation.